Effective treatment method for waste in preparation of water glass from silica fume under normal pressure
Through acid leaching, the calcium ions in high-calcium microsilicon powder are removed, the metal compounds are recovered by staging filtration, hydrogen dilution and alkaline dissolution process are controlled, and the problems of high-calcium microsilicon powder agglomeration and safe hydrogen emissions are solved, and the preparation of high-modulus water glass and the recycling and reuse of metal elements and alkaline sludge are realized, which improves process safety and resource utilization.
Patent Information
- Application Number
- CN202510057891.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
AI Technical Summary
In the process of preparing high-modulus water glass at normal pressure of microsilicon powder, problems such as high-calcium microsilicon powder agglomeration, safe hydrogen emission, water glass modulus improvement, metal element recovery and alkali sludge reuse have not been effectively solved, which has affected process safety, product quality and resource utilization.
Acid leach is used to remove calcium ions in high-calcium microsilicon powder, and useful metal compounds are recovered through staging filtration, hydrogen is diluted with air, alkaline dissolution process is controlled to increase the modulus of water glass, and alkaline sludge is processed through depolymerization, neutralization and sand grinding to achieve its reuse.
It effectively removes calcium ions in high-calcium microsilicon powder, solves the safety hazards of hydrogen, improves the water glass modulus, realizes the recycling and reuse of metal elements and alkali sludge, improves process safety, product quality and resource utilization, and reduces production costs.
Smart Images

Figure BDA0005241960520000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of treatment of wastes in the preparation of water glass by a normal pressure wet method, and specifically relates to an effective method for treating wastes in the preparation of water glass by microsilica powder at normal pressure. Background Art
[0002] Microsilica fume is a by-product produced during the production of ferrosilicon alloy or industrial silicon. Due to its special volcanic ash properties, it can be used as an additive in concrete, cement, refractory materials, rubber, energy storage and molecular sieves. However, on the one hand, the above-mentioned fields have high requirements for the purity of microsilica fume, and on the other hand, the amount added is extremely limited, and it is impossible to achieve large-scale consumption of microsilica fume. Therefore, the wet method for preparing water glass has become an effective way to consume large quantities of microsilica fume and recycle it as a resource.
[0003] There have been many reports on the wet preparation of water glass by microsilica powder. CN118637631A discloses a method for preparing industrial high modulus water glass using microsilica powder. First, mix the microsilica powder with 37.5wt% hydrochloric acid solution, react at 35-90℃ for 0.5-1h, and wash with water to obtain acid leaching residue. Then add 4-4.5mol / L NaOH solution, the liquid-solid ratio of sodium hydroxide solution to microsilica powder is 2.05mL / g, and the performance of water glass can be obtained as Na2O≥8.2%, SiO2≥26.0%, modulus of 3.2-3.5, iron content ≤50ppm, density of 1.30-1.39g / cm3, and dissolution rate of 93%-96%. CN201110268556.5 discloses a method for preparing water glass by wet process using microsilica powder, wherein microsilica powder and liquid alkali are mixed at a SiO2:NaOH molar ratio of 0.9-1.8:1, the mixed solution is sent to a liquid phase reactor under stirring, steam is introduced into the reactor for heating, and the sodium silicate mixed solution is reacted at a temperature of 70°C-220°C for 0.5h-6h to obtain the sodium silicate mixed solution, the sodium silicate mixed solution is discharged from the reactor, the temperature is adjusted to 50°C-95°C in a liquid buffer tank, and the filtrate is filtered under plate and frame pressure to obtain the water glass with a modulus of 1.8-3.2.
[0004] Microsilica powder can be considered as submicron particles formed during the combustion of silica and carbonaceous reducing agents. Zhi Xin from Beijing University of Science and Technology studied the impurities in microsilica powder and the effects of added guest salts on the preparation of water glass gel. The results showed that the addition of guest salt NaCl reduced the equilibrium potential of the colloid particles and accelerated aging; CaO, Fe2O3 and MgO quickly produced gels through complexation, especially the presence of CaO accelerated the formation of gels. The Ca element in microsilica powder mainly comes from two different processes. One is that CaCl2 needs to be added during the production of industrial silicon. Its purpose is to control the reaction temperature, promote the precipitation of silicon and stabilize the reaction system. This type of calcium accompanies the formation of microsilica powder, and Ca elements exist on both the inner and outer surfaces. On the other hand, Ca(OH)2 is added to the flue gas to remove sulfur from microsilica powder. This type of calcium element is mainly concentrated on the outer surface. Wang Jie from Kunming University of Science and Technology found in his experiment that there is a metal lattice inside a single microsilica powder particle, confirming the presence of a metal phase in the microsilica powder. It has been verified that the metal phase should be elemental silicon. In the process of wet preparation of water glass, elemental silicon reacts with NaOH to release hydrogen. The content of elemental silicon in microsilica powder is about 2%-3%. The presence of hydrogen poses a great safety risk to the process operation.
[0005] During the implementation of the above patent, no treatment measures were proposed for the agglomeration of high-calcium microsilica powder. As the alkali dissolution proceeds, about 0.5-1.0% of the internal calcium will be gradually released and quickly occupy the SiO3 2 -Gel is formed, thereby reducing the modulus of water glass. Secondly, when the reaction temperature is raised to 90℃-100℃, the solution begins to boil, and the release of hydrogen in the system reaches the maximum value. If the reaction container is in a closed state, the accumulation of hydrogen will bring great safety hazards. Finally, the alkali solubility of water glass prepared by microsilica powder is generally 60%-90%. If the remaining 10%-40% of alkali mud cannot be reused, it will still affect the sustainable development of industrial silicon or ferrosilicon alloy industry.
[0006] Therefore, we propose a method for treating the waste liquid from the preparation of water glass with high calcium microsilica powder at normal pressure. Summary of the invention
[0007] The purpose of this technology is to provide a method for treating waste liquid from the preparation of water glass with high calcium microsilica at normal pressure, which solves a series of problems encountered in the process of preparing high modulus water glass with microsilica at normal pressure, such as agglomeration of high calcium microsilica, safe emission of hydrogen, improvement of water glass modulus, recovery of metal elements and reuse of alkali mud, etc., thereby realizing the resource reuse of microsilica, improving process safety, product quality and resource utilization, reducing production costs and promoting the sustainable development of related industries.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A method for preparing water glass with high-calcium microsilica powder at normal pressure and an effective method for treating waste liquid thereof, comprising the following steps:
[0010] Step 1. Add hydrochloric acid solution and dispersant to high-calcium microsilica powder (calcium content of 2%) for acid leaching, and filter to obtain acid leaching waste liquid and filter cake after completion; by acid leaching, more than 94% of calcium and more than 50% of sodium in high-calcium microsilica powder are removed, eliminating the two key elements that affect subsequent processes;
[0011] Step 2. Wash the filter cake obtained in step 1 with deionized water until it is neutral, and mix the waste water generated by washing with the waste liquid after acid leaching in step 1 as the waste liquid for overall treatment;
[0012] Step 3. Adding a pH regulator to the waste liquid in step 2, respectively obtaining precipitations of Al(OH)3 and Fe(OH)2 according to the pH value, and concentrating and evaporating the final filtrate produced after the precipitation is filtered to obtain anhydrous calcium chloride; the waste liquid produced is regulated by pH value, and useful metal compounds are recovered while neutralizing the acidic waste liquid to offset the cost of acid leaching;
[0013] Step 4. Add the neutral filter cake obtained in step 2 into the reactor, add deionized water at the same time, control the solid ratio of the system, and then heat it to 50°C-90°C for dispersion; then, introduce preheated gas into the reactor, add additives and caustic soda flakes at the same time, and heat it until the solution boils after the caustic soda flakes are added; finally, control the evaporation amount of water vapor, cool it down and filter it after reaching a certain value, and filter to form water glass solution and alkali mud;
[0014] By adding deionized water, additives and caustic soda to the filter cake, the preparation of high modulus water glass under normal pressure is completed by volatilization of water vapor at high temperature. Since the filter cake contains 2wt%-3wt% of crystalline silicon, it can produce hydrogen with caustic soda solution at a certain temperature. Preheating gas is introduced into the reactor to avoid the explosion of hydrogen. The reaction is heated to the boiling point of the solution, the purpose of which is to evaporate water vapor, continuously increase the concentration of caustic soda and continuously dissolve silicon dioxide, so as to achieve the purpose of preparing high modulus water glass;
[0015] Step 5. The alkali sludge formed in step 4 is directly crushed without washing, caustic soda is added for depolymerization, and then filtered to separate the remaining large particles;
[0016] Step 6. Adding sand milling balls and dispersants to the filtrate after filtering in step 4 to further refine the particles in the filtrate; then, adding a dilute sulfuric acid solution to the filtrate to complete the modification of the surface of the particles in the filtrate;
[0017] Step 7. washing the modified filtrate with deionized water, and then spray drying to form a powder for use as a rubber additive;
[0018] Alkali mud contains a certain amount of water glass solution, which will cause compaction after being filtered by a plate and frame filter press. After being crushed, caustic soda is added, the purpose of which is to rely on caustic soda to depolymerize Si-O-Si bonds. After that, the particles are further refined and sphericalized by the synergistic effect of sand milling balls and dispersants to reduce the wear during application. The refined particles containing water glass react with sulfuric acid, and the particles are coated by the sol-gel process to achieve the purpose of increasing the specific surface area of the particles and the surface hydroxyl content, so as to increase the cross-linking with rubber.
[0019] Furthermore, in step 1, the molar ratio of hydrochloric acid to calcium in microsilica powder is 1.5-3.5:1 (calculated as 80%-90% calcium removal rate), preferably 1.8-2.0:1, and the solid-liquid ratio of microsilica powder to hydrochloric acid solution is 1:1.0-4.0, preferably 1:2.5-3.5.
[0020] Furthermore, the dispersant in step 1 is selected from acid-resistant dispersants such as sodium pyrophosphate, sodium guanidino-4-methylnitrile sulfonate, sodium polymetaphosphate, sodium methyldimethylamine sulfonate, sodium tartrate, and sodium orthophosphate. It can be one of them or a combination of the two; preferably sodium methyldimethylamine sulfonate; the amount of dispersant added is 0.05wt%-0.5wt% (mass ratio of dispersant to microsilica powder), preferably 0.08wt%-0.2wt%.
[0021] Furthermore, the acid leaching reaction time in step 1 is 1.0h-3.0h.
[0022] Furthermore, the pH adjuster described in step 3 can be one of ammonia water, calcium oxide, potassium hydroxide, calcium hydroxide, sodium silicate, potassium silicate, sodium phosphate, potassium phosphate, sodium carbonate, potassium carbonate, etc., and can be a solid or a saturated solution, or a mixture of the two, preferably CaO solid powder.
[0023] Furthermore, the dispersion temperature in step 4 is preferably 70°C-85°C.
[0024] Furthermore, the preheating gas in step 4 is selected from inert gases such as air, nitrogen, helium, etc., preferably air.
[0025] Furthermore, the additive in step 4 is selected from CO3 2- , HCO 3- , Cl - 、F - and PO4 3- The water-soluble acid or sodium salt of the ion is preferably sodium carbonate.
[0026] Furthermore, in step 4, the caustic soda flakes may be added in the form of a solid or a solution, depending on the process. The caustic soda flakes are added for a time of 0.5 h to 3 h, preferably 1.0 h to 2.0 h. After the caustic soda flakes are added, the temperature is slowly raised to 70°C to 115°C, preferably 90°C to 110°C.
[0027] Furthermore, in step 4, the evaporation amount of the system reaches 5%-40%, preferably 15%-35%, and more preferably 20%-35% within 0.5h-3.0h.
[0028] Furthermore, the filtration temperature in step 4 is between 40°C and 80°C, preferably between 50°C and 60°C.
[0029] Furthermore, the mass fraction of caustic soda added in step 5 is 2wt%-10wt%, preferably 4wt%-8wt%, and the reaction lasts for 1.0-2.5h.
[0030] Furthermore, in step 5, sand grinding balls and dispersants are added, the mass ratio of sand grinding balls to alkali mud is 1-5:1, preferably 2-3.5:1, and the amount of dispersants added is 0.1wt%-1wt%, preferably 0.3wt%-0.5wt%. The dispersants are selected from sodium hexametaphosphate, sodium pyrophosphate, sodium polycarboxylate, sodium naphthalenesulfonate, calcium phosphate, or a combination of the two, preferably sodium naphthalenesulfonate.
[0031] Furthermore, the mass fraction of the dilute sulfuric acid solution added in step 7 is 3wt%-20wt%, and the pH value of the reaction system is controlled to be between 3.5-7.0, preferably between 4.5-5.5.
[0032] In summary, due to the adoption of the above technical solution, the beneficial technical effects of the invention are:
[0033] An effective method for preparing water glass with microsilica powder at normal pressure and its waste and hydrogen treatment, using acid leaching to complete Ca 2+ 90%-95% of ions are removed, basically removing the impact of the main impurity ion gel. The waste liquid produced by acid leaching is filtered and precipitated with metal ions, which can achieve the recycling of CaCl2 and complete the metal Al 3+ and Fe 2+Recycling. In the alkali dissolution process, the air is used to dilute and carry hydrogen, which completely solves the hidden dangers of production safety caused by hydrogen. With the volatilization of water vapor, the concentration of alkali gradually increases, the positive trend of the reaction continues to strengthen, and the equilibrium reaction formed is continuously destroyed. This is the key to the water glass modulus reaching more than 3.3. The residual alkali mud does not need to be washed to avoid increasing production costs. The alkali mud is treated with special processes such as depolymerization, neutralization, and sand grinding to make its particle size, specific surface area, oil absorption value, and conductivity meet the requirements of rubber additives. It can partially or completely replace the existing rubber additives, and truly realize the resource recycling of microsilica powder. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the invention more clear, the invention is further described in detail below in combination with the embodiments. It should be understood that the specific embodiments described here are only used to explain the invention and are not used to limit the invention.
[0035] Example 1
[0036] Weigh 30g of microsilica powder with a SiO2 content of 78.1% and calcium 11.5wt% (calculated as calcium oxide) into an acid leaching reactor, add 60mL of 8.5wt% hydrochloric acid solution and 0.03g of sodium methyldimethylamine sulfonate in sequence, raise the temperature to about 70°C, react for 1.5h, then cool to room temperature for filtration, and wash with distilled water until neutral.
[0037] 51.6g of the wet filter cake washed to neutrality (including 25.8g of microsilica powder) was transferred to a water glass reactor, and 51.6g of distilled water (W1) was added and the temperature was slowly raised to 83°C. The flue was gradually opened to introduce air at a temperature of 40°C, and the air flow rate was 377.14mL / min (V1). 0.25g of Na2CO3 solid was added, and 7.64g (W2) of sodium hydroxide was gradually added to the reactor. The addition time of NaOH was controlled within 70min. According to the change of reaction temperature, the temperature was gradually adjusted to 93°C and then the reaction was carried out at a constant temperature. When the collected condensed water reached 30% of the total amount of water added, the reaction was stopped, and the temperature was gradually lowered to 50°C and filtered. The water glass solution was collected and the modulus and solid content were determined. The alkali mud was dispersed, sand-milled and neutralized to complete the modification of particle size and specific surface area, and then spray-dried to obtain dry alkali mud powder, and the particle size and specific surface area were tested, and then stored for application in rubber additives.
[0038] Weigh 60g of waste liquid into the reactor, add 3.4g of Ca(OH)2 powder solid to make the pH value of the solution reach 3. Add the saturated solution of Ca(OH)2 dropwise, and stop adding the alkali solution when the pH value of the solution reaches about 4.3, and obtain the precipitation of Al(OH)3 by centrifugal filtration. Continue to add the saturated solution of Ca(OH)2 to the filtrate, and stop adding the alkali solution when the pH value of the solution reaches about 7.5, and obtain the precipitation of Fe(OH)2 by centrifugal filtration. Cool the filtrate and crystallize to obtain CaCl2 or CaCl2·2H2O. The test results are shown in Table 1.
[0039] The calculation is as follows:
[0040] (1)W1
[0041] According to the 105°C ignition reduction experiment, the water content of the filter cake is about 50%. Based on the solid-liquid ratio of 1:3, the distilled water that needs to be added is M2=30*0.86*2=51.6g.
[0042] (2)W2
[0043] Designed according to the water glass modulus of 3.6, the alkali dissolution rate of microsilica powder is approximately 80% according to experimental values, and the mass of NaOH added is M3=25.8*0.8*2*40 / 3.6 / 60=7.64g.
[0044] (3) V1
[0045] According to experiments, the Si element in microsilica powder is about 2%, V = 25.8*0.02*2*22.4*366 / 273 / 28 = 1.1L = 1100cm3, the volume of hydrogen produced is 1100cm3, the explosion limit of hydrogen is 4%-75.6%, the addition time of NaOH is calculated as 70 minutes, and the air ventilation volume per minute is V1 = (1100 / 0.04-1100) / 70 = 377.14mL / min.
[0046] Example 2
[0047] Weigh 30g of microsilica powder with 97% SiO2 content and 0.71wt% calcium (calculated as calcium oxide) in a water glass reactor, add 90.0g of distilled water and slowly heat it to 83°C, gradually open the flue, pass preheated air at a temperature of 40°C, the air flow rate is 441.26mL / min (V2), add 0.3g of Na2CO3 solid, and then gradually add 8.62g (W3) of sodium hydroxide into the reactor, and the addition time of NaOH is controlled within 70min. According to the change of reaction temperature, gradually adjust the temperature to 93°C and then react at a constant temperature, collect volatile steam through a condenser, stop the reaction when the condensed water reaches 30% of the total water added, gradually cool to 50°C and filter. Collect the obtained water glass solution and measure the modulus and solid content. The collected alkali mud was dispersed, sand-milled and neutralized to modify the particle size and specific surface area, and then spray-dried to obtain dry alkali mud powder, and the particle size and specific surface area were tested, and then stored for application in rubber additives. The test results are shown in Table 1.
[0048] The calculation is as follows:
[0049] W3:
[0050] The modulus of water glass is set to 3.6, the alkali dissolution rate of microsilica powder is about 80% according to experimental values, and the mass of NaOH added is M3=30*0.97*0.8*2*40 / 3.6 / 60=8.62g.
[0051] V2:
[0052] According to experiments, the Si content in microsilicon powder is about 2%, V = 30*0.02*2*22.4*366 / 273 / 28 = 1287cm 3 The volume of hydrogen produced is 1287cm 3 The explosion limit of hydrogen is 4%-75.6%. The addition time of NaOH is calculated as 70 minutes, and the air ventilation volume per minute is V2=(1287 / 0.04-1287) / 70=441.26mL / min.
[0053] Comparative Example 1
[0054] Weigh 30g of microsilica powder with a SiO2 content of 97% and calcium of 0.71wt% (calculated as calcium oxide) in a water glass reactor, add 90.0g of distilled water, heat to 50°C, and react at a constant temperature for 0.5h. Slowly heat to 83°C, gradually open the flue, and gradually add 8.62g of sodium hydroxide into the reactor to prevent hydrogen from being released too quickly and causing safety accidents. The addition time of NaOH is controlled within 70min. According to the change of reaction temperature, gradually adjust the temperature to 93°C and react at a constant temperature for 2h. Gradually cool to 50°C and filter. Collect the water glass solution and measure the modulus and solid content. The test results are shown in Table 1.
[0055] Comparative Example 2
[0056] Weigh 30g of microsilica powder with a SiO2 content of 97% and calcium content of 0.71wt% (calculated as calcium oxide) in a water glass reactor, add 90.0g of distilled water, heat to 83°C, and gradually open the flue. First, add 0.3g of Na2CO3 solid, and then gradually add 8.62g of sodium hydroxide into the reactor to prevent hydrogen from being released too quickly and causing safety accidents. The addition time of NaOH is controlled within 70min. According to the change of reaction temperature, gradually adjust the temperature to 93°C and react at a constant temperature. After 2h of constant temperature reaction, gradually cool to 50°C and filter. Collect the water glass solution and measure the modulus and solid content. The test results are shown in Table 1.
[0057] Comparative Example 3
[0058] Weigh 30g of microsilica powder with a SiO2 content of 78.1% and calcium content of 11.5wt% (calculated as calcium oxide) into an acid leaching reactor, add 60mL of 8.5wt% hydrochloric acid solution in turn and raise the temperature to about 70°C. After reacting for 1.5h, cool to room temperature and filter, and wash with distilled water until neutral.
[0059] 51.6g of filter cake washed to neutrality (including 25.8g of microsilica powder) was transferred to a water glass reactor, and 51.6g of distilled water was added and the temperature was raised to 83°C. Preheated air at a temperature of 40°C was introduced, and the air flow rate was 377.14mL / min. The flue was gradually opened. 7.64g of sodium hydroxide was gradually added to the reactor, and the addition time of NaOH was controlled within 70min. According to the change of reaction temperature, the temperature was gradually adjusted to 93°C and then the reaction was carried out at a constant temperature. The volatile steam was collected by the condenser. When the collected condensed water reached 30% of the total amount of water added, the reaction was stopped, and the temperature was gradually lowered to 50°C and filtered. The water glass solution was collected and the modulus and solid content were determined. The collected alkali mud was dispersed, sand-milled and neutralized to complete the modification of particle size and specific surface area, and then spray-dried to obtain dry alkali mud powder, and the particle size and specific surface area were tested, and then stored for application in rubber additives. The test results are shown in Table 1.
[0060] Comparative Example 4
[0061] Weigh 30g of microsilica powder with a SiO2 content of 78.1% and calcium content of 11.5wt% (calculated as calcium oxide) into an acid leaching reactor, add 60mL of 8.5wt% hydrochloric acid solution and 0.1wt% sodium methyldimethylamine sulfonate in sequence, raise the temperature to about 70°C, react for 1.5h, then cool to room temperature for filtration, and wash with distilled water until neutral.
[0062] Transfer 51.6g of the filter cake washed to neutrality (including 25.8g of microsilica powder) to a water glass reactor, add 51.6g of distilled water and heat to 83°C, gradually open the flue, gradually add 7.64g of sodium hydroxide to the reactor to prevent hydrogen from being released too quickly and causing safety accidents, and control the addition time of NaOH within 70min. According to the change of reaction temperature, gradually adjust the temperature to 93°C and react at a constant temperature. After 2h of constant temperature reaction, cool to 50°C and filter, collect the water glass solution and measure the modulus and solid content.
[0063] Weigh 60g of waste liquid into the reactor, add 3.4g of Ca(OH)2 powder solid to make the pH value of the solution reach 3. Add the saturated solution of Ca(OH)2 dropwise, and stop adding the alkali solution when the pH value of the solution reaches about 4.3, and obtain the precipitation of Al(OH)3 by centrifugal filtration. Continue to add the saturated solution of Ca(OH)2 to the filtrate, and stop adding the alkali solution when the pH value of the solution reaches about 7.5, and obtain the precipitation of Fe(OH)2 by centrifugal filtration. Cool the filtrate and crystallize to obtain CaCl2 or CaCl2·2H2O. The test results are shown in Table 1.
[0064] Comparative Example 5
[0065] Weigh 30g of microsilica powder with a SiO2 content of 78.1% and calcium 11.5wt% (calculated as calcium oxide) and transfer it to a water glass reactor. Add 90% distilled water and heat it to 83°C. Pass air with a preheating temperature of 40°C, and the air flow rate is 377.14mL / min. Gradually open the flue. Add 7.69g of sodium hydroxide to the reactor to prevent the release of hydrogen too quickly and cause safety accidents. The addition time of NaOH is controlled within 70min. According to the change of reaction temperature, gradually adjust the temperature to 93°C and react at a constant temperature. Collect volatile steam through a condenser. When the collected condensed water reaches 30% of the total water added, stop the reaction, gradually cool to 50°C and filter. Collect the water glass solution and measure the modulus and solid content. Disperse, sand grind and neutralize the collected alkali mud to complete the modification of particle size and specific surface area, then spray dry to obtain dry alkali mud powder, test the particle size and specific surface area, and then store it for application in rubber additives.
[0066] Weigh 60g of waste liquid into the reactor, add 3.4g of Ca(OH)2 powder solid to make the pH value of the solution reach 3. Add the saturated solution of Ca(OH)2 dropwise, and stop adding the alkali solution when the pH value of the solution reaches about 4.3, and obtain the precipitation of Al(OH)3 by centrifugal filtration. Continue to add the saturated solution of Ca(OH)2 to the filtrate, and stop adding the alkali solution when the pH value of the solution reaches about 7.5, and obtain the precipitation of Fe(OH)2 by centrifugal filtration. Cool the filtrate and crystallize to obtain CaCl2 or CaCl2·2H2O. The test results are shown in Table 1.
[0067]
[0068] The above description is a preferred embodiment of the invention and is not intended to limit the invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the invention should be included in the protection scope of the invention.
Claims
1. An effective method for treating wastes in the process of preparing water glass from microsilica powder at normal pressure, characterized in that: The following steps are involved: Step 1. Add hydrochloric acid solution and dispersant to high calcium microsilica powder for acid leaching, and filter to obtain acid leaching waste liquid and filter cake after completion; Step 2. Wash the filter cake obtained in step 1 with deionized water until it is neutral, and mix the waste water generated by washing with the waste liquid after acid leaching in step 1 as the waste liquid for overall treatment; Step 3. Add a pH regulator to the waste liquid in step 2, and obtain Al(OH)3 and Fe(OH)2 precipitates according to the pH values. The final filtrate produced after the precipitation is filtered is then concentrated and evaporated to obtain anhydrous calcium chloride. The pH value of the waste liquid is adjusted, and useful metal compounds are recovered while neutralizing the acidic waste liquid. Step 4. Add the neutral filter cake obtained in step 2 into the reactor, add deionized water at the same time, control the solid ratio of the system, and then heat it to 50°C-90°C for dispersion; then, introduce preheated gas into the reactor, add additives and caustic soda flakes at the same time, and heat it until the solution boils after the caustic soda flakes are added; finally, control the evaporation amount of water vapor, cool it down and filter it after reaching a certain value, and filter to form water glass solution and alkali mud; Step 5. The alkali sludge formed in step 4 is directly crushed without washing, caustic soda is added for depolymerization, and then filtered to separate the remaining large particles; Step 6. Adding sand milling balls and dispersants to the filtrate after filtering in step 4 to further refine the particles in the filtrate; then, adding a dilute sulfuric acid solution to the filtrate to complete the modification of the surface of the particles in the filtrate; Step 7. Wash the modified filtrate with deionized water, and then spray-dry it to form a powder for use as a rubber additive.
2. The effective method for treating wastes in the process of preparing water glass from microsilica powder at normal pressure according to claim 1, characterized in that: In step 1, the molar ratio of hydrochloric acid to calcium in microsilica powder is 1.5-3.5:1, and the solid-liquid ratio of microsilica powder to hydrochloric acid solution is 1:1.0-4.
0.
3. The effective method for treating wastes in the process of preparing water glass from microsilica powder at normal pressure according to claim 1, characterized in that: The dispersant in step 1 is selected from acid-resistant dispersants such as sodium pyrophosphate, sodium guanidino-4-methylnitrile sulfonate, sodium polymetaphosphate, sodium methyl dimethylamine sulfonate, sodium tartrate, sodium orthophosphate, etc. It can be one of them or a combination of the two; the mass ratio of the dispersant to the microsilica powder is 0.05wt%-0.5wt%.
4. The effective method for treating wastes in the process of preparing water glass from microsilica powder at normal pressure according to claim 1, characterized in that: The acid leaching reaction time in step 1 is 1.0h-3.0h.
5. The effective method for treating wastes in the process of preparing water glass from microsilica powder at normal pressure according to claim 1, characterized in that: The pH regulator described in step 3 can be one of ammonia water, calcium oxide, potassium hydroxide, calcium hydroxide, sodium silicate, potassium silicate, sodium phosphate, potassium phosphate, sodium carbonate, and potassium carbonate. It can be a solid or a saturated solution, or a mixture of the two.
6. The effective method for treating wastes in the process of preparing water glass from microsilica powder at normal pressure according to claim 1, characterized in that The dispersion temperature in step 4 is preferably 70°C-85°C.
7. The effective method for treating wastes in the process of preparing water glass from microsilica powder at normal pressure according to claim 1, characterized in that: The preheating gas in step 4 is selected from air, nitrogen, helium and other inert gases; the additive is selected from CO3 2- , HCO 3- , Cl - 、F - and PO4 3- The water-soluble acid or sodium salt of ions; the addition of caustic soda flakes can be in the form of solid or solution, and the addition time of caustic soda flakes is 0.5h-3h; and after the addition of caustic soda flakes is completed, the temperature should be slowly raised to 70℃-115℃.
8. The effective method for treating wastes in the process of preparing water glass from microsilica powder at normal pressure according to claim 1, characterized in that: In step 4, the evaporation amount of the system reaches 5%-40% within 0.5h-3.0h; and the filtration temperature is between 40°C and 80°C.
9. The effective method for treating wastes in the process of preparing water glass from microsilica powder at normal pressure according to claim 1, characterized in that: The mass fraction of caustic soda added in step 5 is 2wt%-10wt%, and the reaction lasts for 1.0-2.5h.
10. The effective method for treating wastes in the process of preparing water glass from microsilica powder at normal pressure according to claim 1, characterized in that: The mass ratio of the sand grinding balls and the dispersant added in step 6 is 1-5:1, and the amount of the dispersant added is 0.1wt%-1wt%; the dispersant is selected from one of sodium hexametaphosphate, sodium pyrophosphate, sodium polycarboxylate, sodium naphthalenesulfonate, calcium phosphate, or a combination of the two; the mass fraction of the dilute sulfuric acid solution added is 3wt%-20wt%, and the pH value of the reaction system is controlled to be between 3.5-7.0.
Citation Information
Patent Citations
Process for preparing water glass from silicon micropowder by using wet method
CN102424394B